Conjugacy of Auroral Oval - Feldstein, Y.I.; Starkov, G.V.; Zverev, V.A. (1974)
P(論文) Results of statistical studies so far made hitherto on the auroral ovals in the northern and southern hemispheres are reviewed. Then, a same analysis method is applied on both northern and southern optical auroras to identify the auroral ovals as a function of magnetic activities. The result shows that a good geomagnetically conjugate relationship of the auroral oval is established. In the end, the configurations of the northern auroral oval at different universal times for different magnetic activities are projected along the real magnetic field lines onto the southern hemisphere surface. departmental bulletin paper